Vibration control of large induction motors using actuators between motor feet and steel frame foundation. (November 2018) - Werner, Ulrich
Highlights: Active vibration control of large induction motors on soft steel frame foundations. Multibody-model of the system, including the active vibration control system. Using actuators between motor feet and steel frame foundation. Avoiding resonances in the operation speed range of the motor. Numerical example: 1.6 MW induction motor. Abstract: In the paper a theoretical analysis is deduced regarding vibration control of large induction motors – power rating ≥1 MW – with roller bearings, using actuators between motor feet and a soft steel frame foundation. Based on a multibody model, the mathematical coherences are shown, including the feedback control system. Afterwards a numerical example of a soft mounted, converter driven, 2-pole induction motor (1.6 MW) with ball bearings is presented, where the bearing housing vibrations and the foundation vibrations are analyzed with and without control system. It could be shown, that without vibration control system the operating speed range cannot be used completely because of resonances, caused by the soft foundation. Therefore, critical speed areas occur, where steady state operation is not possible. However, with the vibration control system, the whole operating speed range can be used. The aim of the paper is to show the capability of using a vibration control system with actuators between motor feet and a soft foundation, for avoiding off-limits areas for the operation speed of large induction motors.